Immune Thrombocytopenia in a Challenging Case of Disseminated Tuberculosis: A Case Report and Review of the Literature. (15th September 2010) - Kalra, Ankur; Kalra, Ankit; Palaniswamy, Chandrasekar; Vikram, Naval; Khilnani, G. C.; Sood, Rita
Abstract : Mycobacterium tuberculosis (MTB) continues to predominate the cause of morbidity, and mortality in the developing world. The disease affects all the organ systems, and presents in various pathologic disease states. We report an uncommon manifestation of this rather common infectious disease in a 19-year-old male. Immune-mediated thrombocytopenia occurring as a consequence of the tuberculosis infection itself is an exceedingly rare occurrence, and at the time of writing of this paper, only 15 such published reports exist in the English literature so far.